Higher Education and Growth Performance of Eastern European Countries - Ozturk, Feride (Asian Journal of Empirical Research, 2015)
This study investigates the causal relationship between higher education and GDP in the Eastern European countries including Bulgaria, Czech Republic, Hungary, Lithuania, Poland, Romania, and Slovenia for the period of 1980-2012. Toda and Yamamoto (1995) causality testing method is applied to determine causal relationship between higher education and GDP. The empirical results show evidence of bidirectional causality between higher education and GDP in Czech Republic and no causality for Bulgaria, Lithuania, and Poland. For Hungary and Sloveniathe causality is unidirectional, running from higher education to GDP. In the case of Romania, it appears that the causality runs from GDP to higher education.